2005
DOI: 10.1158/1055-9965.epi-04-0799
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Human Papillomavirus Type 16 Viral Load and the Prospective Risk of Cervical Precancer and Cancer

Abstract: We examined whether higher human papillomavirus type 16 (HPV16) viral load predicted risk of cervical intraepithelial neoplasia 3 (CIN3) or cancer (together termed z zCIN3) within a cohort of 20,810 women followed for 10 years with cytologic screening. Semiquantitative viral load for HPV16 was measured on baseline cervicovaginal specimens using a type-specific hybridization probe test with signal amplification. An increased risk of z zCIN3 associated with higher HPV16 viral load was found only among cytologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Still, this group may include a small proportion of women with prevalent high-grade CIN lesions missed by cytology. Since we anticipate that such cases would display increased viral copy numbers that fall in the higher viral load percentiles, 19 we consider the sensitivity of the 33rd percentile thresholds set in this study not over represented. It is also noteworthy that total DNA can be derived from many types of cells from the cervix, including inflammatory cells that are not HPV host cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Still, this group may include a small proportion of women with prevalent high-grade CIN lesions missed by cytology. Since we anticipate that such cases would display increased viral copy numbers that fall in the higher viral load percentiles, 19 we consider the sensitivity of the 33rd percentile thresholds set in this study not over represented. It is also noteworthy that total DNA can be derived from many types of cells from the cervix, including inflammatory cells that are not HPV host cells.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11,13,18 Nevertheless, also amongst HPV 16 positive women with normal cytology defined by hc2, semiquantitative viral load assessment could better predict those women who are more likely to have prevalent CIN 3 lesions. 19 Still, most studies had in common a substantial overlap of viral load values amongst women with and without high-grade CIN, especially in the range of high viral loads. This precludes setting a cut-off value for high-grade CIN on the basis of high viral loads.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, several groups have suggested that viral load may be used as a predictor of cervical lesion clearance. 12,16,18,30 A word of caution should be taken, however, since high viral load values with normal cytology may represent equivocal diagnosis of cervical lesions, 23 and further research is needed.…”
Section: Discussionmentioning
confidence: 99%